Damage effects of aluminum plate by reactive material projectile impact. (June 2017) - Xu, F.Y.; Zheng, Y.F.; Yu, Q.B.; Zhang, X.P.; Wang, H.F.
Highlights: Petalling damage is formed in thin plates impacted by reactive projectile in velocity range from 289 to 482 m/s. Plugging damage is formed in thick plates impacted by reactive projectile in velocity range from 500 to 956 m/s. Height of petal bulge and penetration hole diameter in plates are influenced by impact velocity. Chemical energy release of reactive materials during penetration may enhance lethality to a plate. Abstract: This investigation describes and analyzes the damage effects of 2024-T3 aluminum plates normally impacted by cold isostatically pressed and sintered PTFE/Al/W reactive material projectiles. In the experiments, the reactive material projectiles impacted 3 mm thick aluminum plates at velocities in the range from 289 to 569 m/s and impacted 12 mm thick aluminum plates at velocities in the range from 500 to 956 m/s. The damage patterns and the corresponding penetration-induced deflagration behavior are presented and analyzed. In addition, combining theoretical considerations with experimental results, the effect of impact velocity on the extent of petal bulge and the penetration hole sizes is analyzed. Moreover, by comparing the calculated results with the experimental data, the influences of chemical energy released from the reactive materials during penetration on the extent of petal bulge and the penetration hole sizes are investigated and discussed. As the results show, the damage of aluminum plates by reactive material projectile impact not only varies with the kinetic energy, but is also significantly influenced by the chemical energy released in the penetration process.